New class of spin projection operators for 3D models - Accioly, Antonio [UNESP]; Helayël-Neto, José; Pereira-Dias, Bruno; Hernaski, Carlos (American Physical Society (APS), 2012)
A new set of projection operators for three-dimensional models are constructed. Using these operators, an uncomplicated and easy handling algorithm for analyzing the unitarity of the aforementioned systems is built up. Interestingly enough, this method converts the task of probing the unitarity of a given three-dimensional system, which is in general a time-consuming work, into a straightforward algebraic exercise; besides, it also greatly clarifies the physical interpretation of the propagating modes. To test the efficacy and quickness of the algorithm at hand, the unitarity of some important and timely higher-order electromagnetic (gravitational) systems augmented by both Chern-Simons and higher order Chern-Simons terms are investigated. © 2012 American Physical Society.